The Dialectical Return of Vocational Teacher Education Model in Germany - Yuan-Chuan Chang (National Taipei University of Education, 2020)
This paper explores the development trend of the German vocational teacher education model through document analysis, and focuses on the theoretical teachers of vocational schools. In the early stage, training was mainly conducted in the context of an apprentice-master relationship, in which the master craftsman personally imparted the knowledge and skills which would enable the apprentice to advance to the stage of craftsmanship and become a master craftsman. In the middle stage, ushered in by the industrial revolution and the resulting establishment of a large number of vocational schools, vocational teacher education was divided into three areas: practical skills, engineering, and pedagogy, and gradually tended to be systematic "discipline-oriented". In the advanced stage, the increasing emphasis on professional specialization led to far-reaching changes and the adoption of a "work process" orientation, which discarded the concept of a systematized branch of learning in favor of professional competence, and revived the emphasis on hands-on work of the early stage. However, in the advanced stage the structure and content of vocational teacher education are based on the needs and outlook of modern science, whereas in the early stage more importance was given to the apprentice's individual interests. Thus, the development of vocational teacher education can be said to exhibit a dialectical return. German teacher education includes the cooperation of many institutions, which provides a good reference for Taiwan's vocational education teacher education reform.